Research technology of cultivation of spirulina algae with the use of CO2 hidden from the smoke of rice husk boiler - Trinh , Van Dung; Phan, Quoc Thinh; Nguyen , Quoc Dat; Pham , Van Hung (Journal of Technical Education Science, 2021)
This paper presents an investigation of Spirulina algae cultivation by the CO2 gas emitted from the combustion of rice husk. The gas emitted from the rice husk combustion containing CO2 but no toxic gas of SOx. The CO2 molecules are absorbed into the micro-algae cultivation medium and then converted into the HCO3 by the assimilation of Spirulina. At the same time, the pH values are controlled to be from 8.5 to 9.5, which is suitable for Spirulina algae. At the first seven days of cultivation in Zarrouk medium the values of Spirulina algae biomass and pH increase from 0.05 g/l and 8.5 to 1.0 g/l and 10.2, respectively. On the 8th day, when the amount of 7,6 % CO2 v/v under 35–40 ºC and 1 atm is introduced into the above medium, the decrease of pH from 10.2 to 8.6 is observed. This pH value, which is maintained over the following days, is optimal for the growth yield of the Spirulina. As a result, the biomass concentration increases from 1.0 to 1.4 g/l. The obtained results are compared with those of the control sample from Zarrouk medium without gas introduction. For the latter case, the biomass reaches the maximum and then decreases. On the basis of the obtained results, the cultivation of Spirulina algae by using the CO2 molecules emitted from the combustion of rice husk can be applied practically.